Produtividade dos fatores de produção na pecuária de corte em Minas Gerais - Batista de Oliveira , Evonir; Coelho de Alvarenga , Sônia; Ávila Pires , José Alberto; Rodrigues Pereira , Raimundo (Revista Ceres, 2025)
This study deals with the economic analysis of resource use in beef production in seven regions of the State of Minas Gerais.